Killing for God: Akers’ Social Learning Theory Applied to the Case of Daniel Lafferty - Eleanor, Kate (Journal of Leadership, Accountability and Ethics, 2020)
Akers’ Social Learning Theory (SLT), esteemed among the general theories of crime, provides an overarching framework for understanding the development of criminal attitudes and behaviors. This paper utilizes a case study approach to view a double homicide committed in the name of religious ideology through the theoretical lens of SLT. Examination of the subject’s upbringing sheds light on his vulnerability to influence and potential to do harm. In an era of increasingly divergent ideologies, the application of Social Learning Theory can illuminate the process of radicalization, help identify those at risk, and suggest potential points of intervention